1977
DOI: 10.1149/1.2133519
|View full text |Cite
|
Sign up to set email alerts
|

EMF Studies of Lithium‐Rich Lithium‐Aluminum Alloys for High‐Energy Secondary Batteries

Abstract: Emf measurements were made across the lithium-rich half of the lithiumaluminum system at temperatures from 390 ~ to 550~ using a cell of the type Li/LiC1-KC1 (or LiF-LiC1-LiBr)/Li-A1. The lithium activity increases from 0.007 to approximately 0.7 over the composition range of 48-56 atomic percent (a/o) lithium (the E-phase region). A compound, Li3A12, rather than Li2A1, as reported in standard compilations, exists at temperatures up to the peritectic decomposition at 520r and forms a two-phase region of high l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

1977
1977
2008
2008

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 7 publications
2
31
0
Order By: Relevance
“…% into the B-LiAl phase, the potential decreases very rapidly and approaches that of lithium. 3 The theoretical capacity of Li-Al containing 47 at. % lithium, which has a density of 1.75 g/cm3, is approximately 0.74 Ah/g or 1.3 Ah/cm 3 when the material is discharged to 10 at.…”
Section: Negative Electrodementioning
confidence: 99%
See 2 more Smart Citations
“…% into the B-LiAl phase, the potential decreases very rapidly and approaches that of lithium. 3 The theoretical capacity of Li-Al containing 47 at. % lithium, which has a density of 1.75 g/cm3, is approximately 0.74 Ah/g or 1.3 Ah/cm 3 when the material is discharged to 10 at.…”
Section: Negative Electrodementioning
confidence: 99%
“…The theoretical capacity of these multiplate cells (two positive and three negative plates) was about 200 Ah. The negative electrodes of LiAl + Al were pressed to a capacity loading density of about 1.3 Ah/cm 3 , based on the fully charged state (and no expansion).…”
Section: Post-test Cell Examinationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in any actual battery there will be an excess of lithium present, able to dissolve the aluminum or silicon produced by these reactions. In order to estimate the magnitude of this extra free energy of solution, calculations were performed based on available literature data for the activities of silicon [9] and aluminum [10], in molten lithium. Thus, under these conditions the silicate seems certain to dissolve in molten lithium at 700 K, and the aluminate case is finally balanced but attack by the lithium is a possibility.…”
Section: Thermodynamic Stability Of Lithium Solid Electrolytesmentioning
confidence: 99%
“…Emf measurements by Yao et al [ 16 ] showed a constant voltage of 300 mV versus pure lithium for this two phase region; more recent measurements of Selman [ 10 ] was used for the measurements. Lithium was added to, or removed from, the beta lithium aluminum working electrode and the emf versus composition curve shown in Figure 2 was obtained.…”
Section: ) Lithium-antimony and Lithium-bismuth Intermetallic Systemsmentioning
confidence: 99%